The optimal port privatization levels under inter-port competition: Considering both horizontal and vertical differentiation - Wei Wang; Xiujuan Liu; Lili Ding; Chen Li; Wensi Zhang (Kiel Institute for the World Economy (IfW), 2018)
The authors examine a mixed duopoly market with Cournot or Bertrand competition between a purely private port (port 1) and a partial public port (port 2). Considering both horizontal and vertical differentiation between the two ports, they analytically derive the welfare effect of privatization of port 2 and determine the optimal degree of privatization. Under Cournot or Bertrand competition, it is demonstrated that the social desirable private level of port 2 varies among full privatization, partial privatization and full nationalization, which hinges mainly upon the market size, both horizontal and vertical differentiation between the two ports and the marginal operation cost of each port. As a result, there is not necessarily a one-size-fits-all strategy for port privatization, and it is important for policymakers to consider the effects of market demand, port competition factors in port privatization.
Keywords: D43; L33; 330; port; competition; privatization; horizontal and vertical differentiation